Perceptual learning, talker specificity, and sound change - Tamminga, Meredith; Wilder, Robert; Lai, Wei; Wade, Lacey (Papers in Historical Phonology, 2020)
Perceptual learning is when listeners hear novel speech input and shift their subsequent perceptual behavior. In this paper we consider the relationship between sound change and perceptual learning. We spell out the connections we see between perceptual learning and different approaches to sound change and explain how a deeper empirical understanding of the properties of perceptual learning might benefit sound change models. We propose that questions about when listeners generalize their perceptual learning to new talkers might be of of particular interest to theories of sound change. We review the relevant literature, noting that studies of perceptual learning generalization across talkers of the same gender are lacking. Finally, we present new experimental data aimed at filling that gap by comparing cross-talker generalization of fricative boundary perceptual learning in same-gender and different-gender pairs. We find that listeners are much more likely to generalize what they have learned across same-gender pairs, even when the different-gender pairs have more similar fricatives. We discuss implications for sound change.